The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1590/s2179-975x2014000200002
|View full text |Cite
|
Sign up to set email alerts
|

The influence of environmental variables on spatial and temporal phytoplankton dissimilarity in a large shallow subtropical lake (Lake Mangueira, southern Brazil)

Abstract: Aim:The uneven distribution of organisms in aquatic ecosystems is generally attributed to environmental heterogeneity in both space and time, reflecting the occurrence of appropriate environmental conditions and the availability of resources to biological communities. The aim of this study was to understand how the dissimilarity of the phytoplankton community in a large subtropical shallow lake is related to environmental dissimilarities. Methods: Biotic and environmental data were gathered at 19 sites along t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 36 publications
3
8
1
Order By: Relevance
“…The homogeneity in the phytoplankton distribution in this study could be attributed to the similarities in the nitrate concentrations in the sampling stations. This is confirmed by the statement according to Halterman and Toetz (1984), Tilman et al (1986), and Crossetti et al (2014) that dissimilarities in nitrate availability may lead to differences in phytoplankton structure, since half-saturation concentrations for nitrate uptake may vary among phytoplankton species.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The homogeneity in the phytoplankton distribution in this study could be attributed to the similarities in the nitrate concentrations in the sampling stations. This is confirmed by the statement according to Halterman and Toetz (1984), Tilman et al (1986), and Crossetti et al (2014) that dissimilarities in nitrate availability may lead to differences in phytoplankton structure, since half-saturation concentrations for nitrate uptake may vary among phytoplankton species.…”
Section: Discussionsupporting
confidence: 70%
“…Similarly, Nowrouzi and Valavi (2011) observed positive correlation of nutrient (especially nitrate) with phytoplankton abundance in Lake Kalfter. Crossetti et al (2014) reported that the combination of environmental variables that best correlates with the dissimilarities observed in phytoplankton distribution in Lake Mangueira, southern Brazil were pH, turbidity, and nitrate. Similarly, nutrients, pH, conductivity andwater temperature were the set of environmental variables that best explained variationsin phytoplankton functional groups in Lake Mangueira in a six year data set (Crossetti et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Approaches based on species traits have shown which groups of species have distinct responses according to their biological traits (Heino et al ; Tonkin et al ; Campos et al ). Reynolds functional groups (RFGs, supported by Kruk et al ), for example, are sensitive to environmental variation, and in this sense, trait‐based approaches have been increasingly applied to explain and predict the response of phytoplankton species to environmental conditions in aquatic systems (Nabout et al ; Crossetii et al ; Rangel et al ; Bortolini et al ). These approaches can enable the detection of patterns and underlying processes, which might not be detectable when studying the structure of the entire community (Stenger‐Kovács et al ; Vilmi et al ).…”
Section: Introductionmentioning
confidence: 99%
“…(light and nutrients), in spatially heterogeneous environments have been related to phytoplankton functional diversity (Caputo et al, 2008;Rychtecký & Znachor, 2011;Crossetti et al, 2014). In this sense, the present study aimed at evaluating the influence of spatial and temporal heterogeneity on the functional structure of the phytoplankton community in a large subtropical shallow lake.…”
Section: Introductionmentioning
confidence: 99%